2021
DOI: 10.26897/2687-1149-2021-4-33-40
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Microarc Oxidation Coating Growth in the No-Bath Process

Abstract: The authors consider theoretical foundations of the coating formation when using the no-bath method of microarc oxidation (MAO) as applied to a point counter electrode. The relationships between the growth rate of the coating thickness and the electrical, geometric and chemical parameters of the MAO process have been mathematically determined. An algorithm for calculating the productivity of the MAO process, due to the growth rate of the coating thickness has been developed. The off ered methodology for the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the aerospace industry, the maximum reduction in the mass of the structure being developed is important, so even the replacement of individual elements is of great importance. In particular, it has been shown that replacement of steel or titanium in the spacecraft opening jaws by micro-arc oxidationmodified aluminium alloy AMg6M is justified [9]. Hardened parts made of lightweight structural material provide high reliability of the unit operation under conditions of vibration loads, increased wear, low temperatures and vacuum.…”
Section: Main Applications Of Microplasma Electrolytic Oxidation Tech...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the aerospace industry, the maximum reduction in the mass of the structure being developed is important, so even the replacement of individual elements is of great importance. In particular, it has been shown that replacement of steel or titanium in the spacecraft opening jaws by micro-arc oxidationmodified aluminium alloy AMg6M is justified [9]. Hardened parts made of lightweight structural material provide high reliability of the unit operation under conditions of vibration loads, increased wear, low temperatures and vacuum.…”
Section: Main Applications Of Microplasma Electrolytic Oxidation Tech...mentioning
confidence: 99%
“…Modification by microplasma electrolytic oxidation of aluminum parts to protect them from aggressive environments: chemically active solutions, seawater, extreme weather conditions, etc. [3,9,10,18]. It was found in [19] that, at temperatures up to 870°C, MAO coatings on titanium alloy Ti-6Al−4V 45-50 µm thick, retained high adhesion to the substrate and surface density without signs of pitting.…”
Section: Main Applications Of Microplasma Electrolytic Oxidation Tech...mentioning
confidence: 99%
See 1 more Smart Citation